"MitoTea": Geranium robertianum L. decoctions decrease blood glucose levels and improve liver mitochondrial oxidative phosphorylation in diabetic Goto-Kakizaki rats - Santos, Maria Sancha (2010)
Several chemical compounds found in plant products have proven to possess beneficial properties, being currently pointed out due to their pharmacological potential in type 2 diabetes mellitus complications. In this context, we studied the effect of Geranium robertianum L. (herb Robert) leaf decoctions in Goto–Kakizaki (GK) rats, a model of type 2 diabetes. Our results showed that oral administration of G. robertianum leaf decoctions over a period of four weeks lowered the plasma glucose levels in diabetic rats. Furthermore, the treatment with G. robertianum extracts improved liver mitochondrial respiratory parameters (state 3, state 4 and FCCP-stimulated respiration) and increased oxidative phosphorylation efficiency.